BRCA1 and BRCA2 Tumor Suppressor Function in Meiosis - Li, Qianyan; Engebrecht, JoAnne (Frontiers in Cell and Developmental Biology, 2021)
Meiosis is essential for sexual reproduction and results in halving of the genome for packaging into gametes. During meiosis, homologous chromosomes are connected through the repair of double strand breaks by homologous recombination to form crossovers, which facilitate alignment on the meiotic spindle and proper chromosome segregation. While it is well established that the tumor suppressors BRCA1 and BRCA2 function in DNA repair and recombination in somatic cells, the functions of BRCA1 and BRCA2 in meiosis have received less attention. Recent studies in both mouse and the simple metazoan Caenorhabditis elegans have provided insight into the role of these tumor suppressors in a number of meiotic processes, revealing both conserved and unique roles in different organisms. BRCA1 forms an E3 ubiquitin ligase as a heterodimer with BARD1 and is essential for Meiotic Sex Chromosome Inactivation, the process whereby hemizygous regions of sex chromosomes are transcriptionally silenced, in mammalian male meiosis, but not in C. elegans. On the other hand, BRCA1-BARD1 regulates DNA end resection for homologous recombination in C. elegans male germ cells but does not appear to regulate resection in mouse spermatocytes. C. elegans BRCA1-BARD1 also regulates the crossover landscape. BRCA2 is a very large protein that plays an intimate role in homologous recombination. During meiosis, BRCA2 functions in a complex, at least in mammals, and promotes the exchange of RPA for the recombinases DMC1/RAD51 at meiotic DSBs in both mammals and C. elegans. As women carrying BRCA mutations with no indication of cancer show decreased ovarian reserve and accumulated oocyte DNA damage, studies in these systems may provide insight into why BRCA mutations impact reproductive success in addition to their established roles in cancer.